A cross-sectional investigation of the mental health and wellbeing among individuals who have been negatively impacted by the COVID-19 international border closure in Australia - Kathina Ali; Matthew Iasiello; Joep van Agteren; Teri Mavrangelos; Michael Kyrios; Daniel B. Fassnacht (BMC, 2022)
Abstract Background The COVID-19 pandemic resulted in the Australian government implementing strict international border closures. However, research has not yet investigated the mental health status of individuals impacted negatively by these international border closures. Methods The present study was a cross-sectional online survey of 3968 adults who reported being negatively affected by the border closure during June and July 2021. Psychological distress was measured with the Kessler Psychological Distress Scale (K10), stress with the Perceived Stress Scale (PSS) and wellbeing with the Mental Health Continuum Short Form (MHC-SF). Results In total, 3968 participants reported being negatively affected by the current restrictions (63.4% in Australia, 36.6% overseas). The vast majority of respondents (83.6%) reported high or very high levels of psychological distress (mean K10 score > 22), and 74.8% reported poor mental wellbeing, with similar risk profiles for participants in Australia or overseas. The most common scenarios of affected individuals included 1) wanting to enter Australia (30.8%), 2) wanting to leave Australia (29.6%) and 3) wanting someone to enter Australia (25.6%). Reasons included wanting to be with partners, family and friends (81.1%), for employment/economic reasons (4.9%), study (4.1%), personal safety/health (2.6%) or holiday (1.4%). While psychological distress was extremely high across all groups, separated partners and those with interrupted study experienced the highest distress (mean K10 = 35.7, n = 155). Conclusion The data suggests a highly elevated mental health risk profile among individuals who report being negatively affected by current Australian international border closures. The results provide valuable data to inform future policy decisions and have clear implications regarding effective service provision for this vulnerable group.